Local Finance: Financial Resources Problem in Thailand - Darunee Pumkaew (Universitas Medan Area, 2019)
This study examines local government revenue in the 2016 fiscal year. The study makes use of local budget allocation documents to analyse problems with local public finance from the Department of Local Administration and employs data collected from four groups, namely government officials, experts, local politicians, and local government officials. This study reveals several findings. First, revenue structure of local government does not reflect self-reliance and fiscal autonomy. Instead the revenue of all types of local administrative organizations (LAOs) rely mostly on grants rather than on their self-collected revenues. Second, local administration organizationsâ€™ revenue between regions is unequal. LAOs in the Northeastern region show the lowest revenues per head from all revenue sources, and grant allocation is not academic-based. The fact that the Northeastern revenue and tax collection is lower than other regions, and that this region is allocated the smallest and fewest grants by the government, is evidence of this. Fourth, finance laws, especially regarding local finance, are outdated. There is no specific legislation on the identification of revenue sources of local administrative organizations, nor is there legislation on the regulation and practice of seeking new revenue sources for these organizations. And fifth, local administrative organizations are incapable of improving the local financial system that includes financial management, staff, and taxpayers.Â Â